Explaining Inflation in Colombia : A Disaggregated Phillips Curve Approach - Lanau, Sergi (IMF Working Papers; Working Paper ;, 2018)
We study inflation dynamics in Colombia using a bottom-up Phillips curve approach. This allows us to capture the different drivers of individual inflation components. We find that the Phillips curve is relatively flat in Colombia but steeper than recent estimates for the U.S. Supply side shocks play an important role for tradable and food prices, while indexation dynamics are important for non-tradable goods. We show that besides allowing for a more detailed understanding of inflation drivers, the bottom-up approach also improves on an aggregate Phillips curve in terms of forecasting ability. In the baseline forecast scenario, both headline and core inflation converge towards the Central Bank's inflation target of 3 percent by end-2018 but these favorable inflation dynamics are vulnerable to large supply shocks.